Breaking up is hard to do: Why the Eurozone will survive - Kevin Aslett; James Caporaso (Economies, 2016)
Since revelations of the Greek fiscal deficit in the fall of 2009, the breakup of the Economic and Monetary Union (EMU) has moved from unthinkable to plausible. The debate over the future of the EMU has become increasingly relevant, as numerous efforts to solve the Greek crisis have not been successful. Neither have basic competitiveness differences between countries in the core and periphery of the European Union been eliminated. Proposed solutions include development of a banking union, regulatory measures to monitor trade and capital imbalances, fiscal reforms on the part of countries in trouble, and centralized fiscal capacity on the part of the EMU itself to offset the liabilities of the indebted states. While the crisis seems to be contained, it is by no means solved. This leads to the question: 'Will the euro survive?' We answer this question in the affirmative, but in doing so we argue that continuation of the EMU is different from the question of whether the EMU should have been created in the first place. Some reasons for continuation of the EMU were present at its creation; others have developed in a path-dependent way as the Eurozone has evolved.
Keywords: E02; F45; F55; 330; European Union; Economic and Monetary Union; financial crisis; path dependency; Eurozone